THE USE OF TURMERIC TAMARIND AS LOCAL WISDOM TO REDUCE DYSMENORRHEA IN ADOLESCENCE: LITERATURE REVIEW - Kinantika Nur Dewanti; Galih Noor Alivian (International Journal of Biomedical Nursing Review, 2024)
Introduction: Local wisdom is part of the culture or wealth that exists in a particular area. Local wisdom covers various things, including a diversity of resources that can be used to overcome health problems. Turmeric Tamarind is a spice plant that can be used as a traditional medicine or health drink to reduce menstrual pain (dysmenorrhea). However, adolescence still don't know the benefits and effects of turmeric tamarind and prefer medication to treat pain. Purpose: This literature review aims to find out the effect of turmeric tamarind to reduce dysmenorrhea in adolescence. Methods: Articles are derived from electronic databases such as Google Scholar and Scopus published from 2020 to 2024. Results: Based on the 10 articles used in this literature review, it shows that turmeric tamarind can reduce dysmenorrhea pain with its anti-inflammatory agent. Conclusion: Turmeric Tamarind as spice plant can be used to reduce dysmenorrhea in adolescence